Compressible Zn–Air Batteries Based on Metal–Organic Frameworks Nanoflake‐Assembled Carbon Frameworks for Portable Motion and Temperature Monitors. Issue 7 (29th March 2022) - Zheng, Dong; Liu, Wenxian; Dai, Xiaojing; Feng, Jinxiu; Xu, Xilian; Yin, Ruilian; Que, Wenbin; Shi, Wenhui; Wu, Fangfang; Wu, Huaping; Cao, Xiehong
Abstract : High‐performance and integrated power sources are critical to the practical application of wearable sensors, enabling monitoring of physical signs in real time. However, realizing both good battery performance and portability for batteries is still a challenge to such integration application. Herein, a novel cathode material of flexible zinc–air battery is developed, i.e., NiFe‐based metal–organic frameworks nanoflakes assembled on the carbon frameworks with nitrogen‐heteroatom dopant (NiFe NF/NCFs). Benefiting from the unique interfacial interaction of 2D materials, as well as the rational integration of multifunctional electrocatalytic components in a flexible and compressible skeleton, the prepared NiFe NF/NCFs exhibits excellent activities for oxygen evolution/reduction reactions. Moreover, it achieves high peak power density (107.2 mW cm −2 ) and specific capacity (814.2 mAh g −1 ) when served as the cathode of zinc–air batteries. Importantly, serving as both battery cathode and sensing unit, a strain sensor–battery integration device is also demonstrated based on the NiFe NF/NCFs, which displays a favorable strain sensitivity toward detecting human motions. This work provides a new pathway to the development of energy storage device for flexible electronics. Abstract : NiFe metal–organic frameworks nanoflake‐assembled nitrogen‐doped carbon frameworks (NiFe NF/NCFs) are reported and serve as electrode for both flexible Zn–air batteries (FZAB) and strain sensor–battery integration devices. The FZAB delivers high peak power density (107.2 mW cm −2 ), and specific capacity (814.2 mAh g −1 ). Moreover, a favorable strain sensitivity towards detecting human motions is demonstrated in a strain sensor–battery integration device.